On development of web application for corpus of archival documents - Pavlov, Artur V; Sapich, Yuliya D; Svetlov, Andrey V; Komendantov, Anatoly S (Mathematical Physics and Computer Modeling, 2022)
This work is a part of the project on creation the linguistic corpus of the fund “Mikhailovsky stanitsa ataman” documents. This fund contains historically valuable administrative documents of the Don Cossacks Army of the 18th-19th centuries, stored in the State Archives of the Volgograd Region. To introduce it to scientific society, a lot of preliminary work to digitize them was done by group of scientists from Volgograd State University headed by Professor O.A. Gorban. In their current form, these documents are suitable for computer processing. The only significant problem is outdated vocabulary and graphics, but it was generally solved in our previous works. At the current stage, the main task is to develop the technical and software parts of the corpus. In fact, this means the creation of an “engine” for a document corpus, that is, software for storing a database of marked-up texts, executing queries to this database, and also providing user-friendly interface that does not require special IT-skills. At the same time, in the process of working on the previous tasks, we decided to integrate the document markup tool into the general corpus software. Thus, the present work is devoted to the development of a REST service that allows you to perform automated morphological analysis of texts, save a special form of processed documents in a database, search in database by a query with morphological features of elements in the texts. The software also provides a function for manual correction of errors that occur in automated analysis of Old Slavonic texts with obsolete characters.